Rational engineering of a thermostable α-oxoamine synthase biocatalyst expands the substrate scope and synthetic applicability - Ben Ashley; Sam Mathew; Mariyah Sajjad; Yaoyi Zhu; Nikita Novikovs; Arnaud Baslé; Jon Marles-Wright; Dominic J. Campopiano (Communications Chemistry)
Abstract Carbon-carbon bond formation is one of the key pillars of organic synthesis. Green, selective and efficient biocatalytic methods for such are therefore highly desirable. The α-oxoamine synthases (AOSs) are a class of pyridoxal 5’-phosphate (PLP)-dependent, irreversible, carbon-carbon bond-forming enzymes, which have been limited previously by their narrow substrate specificity and requirement of acyl-CoA thioester substrates. We recently characterized a thermophilic enzyme from Thermus thermophilus (ThAOS) with a much broader substrate scope and described its use in a chemo-biocatalytic cascade process to generate pyrroles in good yields and timescales. Herein, we report the structure-guided engineering of ThAOS to arrive at variants able to use a greatly expanded range of amino acid and simplified N-acetylcysteamine (SNAc) acyl-thioester substrates. The crystal structure of the improved ThAOS V79A variant with a bound PLP:l-penicillamine external aldimine ligand, provides insight into the properties of the engineered biocatalyst.